Ureaplasma spp. in the adult urogenital tract: clinical significance, limitations of the evidence base, and management strategy - V. A. Vorobev; I. V. Kosova; D. O. Kostyuchenko; D. V. Tukhieva; B. K. Sharakshinov; D. V. Kerner; V. A. Lutsenko (Urology Herald, 2026)
Introduction. Ureaplasma spp. are among the most common colonizers of the human urogenital tract. Their high prevalence as asymptomatic commensals and the widespread use of multiplex PCR panels have substantially complicated the interpretation of positive test results, increased the risk of overdiagnosis, and contributed to inappropriate antibiotic use in the absence of a convincing causal link between microorganism detection and clinical disease. Objective. To critically appraise the evidence on Ureaplasma spp. persistence, their clinical relevance in adults, diagnostic limitations, and practical management strategies. Materials & methods. We performed a narrative review of PubMed/MEDLINE, Google Scholar, and eLIBRARY publications addressing the clinical significance of Ureaplasma spp. in adults. Priority was given to peer-reviewed systematic reviews, clinical guidelines, cohort studies, and reports on antimicrobial resistance; irrelevant and nonpeer-reviewed sources were excluded. Twenty-five references were included in the final bibliography. Results. Ureaplasma spp. possess biological features that promote persistence, including the absence of a cell wall, antigenic variability, the ability to survive intracellularly, and biofilm formation. The strongest evidence of clinical relevance exists for a subset of cases of nongonococcal urethritis in men, in which U. urealyticum is more often than U. parvum associated with symptomatic inflammation, particularly when bacterial load is high and Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, and Trichomonas vaginalis have been excluded. In women, the evidence base is considerably weaker: detection of Ureaplasma spp. frequently occurs in association with bacterial vaginosis and other dysbiotic states and does not, by itself, establish a causal role in cervicitis, chronic dysuria, or infertility. Nucleic acid amplification tests remain the preferred diagnostic method, ideally with species-level differentiation; however, no universally validated quantitative threshold for clinical significance has been established. Most international guidelines do not support routine testing of asymptomatic men and women for Ureaplasma spp. Conclusion. Ureaplasma spp. should be regarded as opportunistic urogenital microorganisms rather than an automatic marker of disease. A rational approach entails avoiding routine screening of asymptomatic carriers, interpreting PCR results in a clinically guided manner, systematically excluding more likely pathogens, and reserving antibiotic therapy for carefully selected symptomatic cases. The narrative design of this review and the heterogeneity of the available evidence limit the generalizability of its practical conclusions.